Global estimate of the prevalence of post-traumatic stress disorder among adults living with HIV: a systematic review and meta-analysis - Lloyd Goldsamt; Chulei Tang; Jingjing Meng; Xueling Xiao; Ann Bartley Williams; Honghong Wang (BMJ Open)
Objectives Although people living with HIV (PLWH) have been disproportionately affected by post-traumatic stress disorder (PTSD), the global prevalence of PTSD among PLWH is unknown. This study aimed to systematically review the prevalence of PTSD among PLWH worldwide and explore variation in prevalence across sociodemographic and methodological factors.Design A meta-analysis using a random-effects model was conducted to pool the prevalence estimated from individual studies, and subgroup analyses were used to analyse heterogeneities.Setting, participants and measures Observational studies providing PTSD prevalence data in an adult HIV population were searched from January 2000 to November 2019. Measurements were not restricted, although the definition of PTSD had to align with the Diagnostic and Statistical Manual of Mental Disorders or the International Classification of Diseases diagnostic criteria.Results A total of 38 articles were included among 2406 records identified initially. The estimated global prevalence of PTSD in PLWH was 28% (95% CI 24% to 33%). Significant heterogeneity was detected in the proportion of PLWH who reported PTSD across studies, which was partially explained by geographic area, population group, measurement and sampling method (p<0.05).Conclusion PTSD among PLWH is common worldwide. This review highlights that PTSD should be routinely screened for and that more effective prevention strategies and treatment packages targeting PTSD are needed in PLWH.